Penggunaan metode mind mapping dalam keterampilan menulis teks eksplanasi di SD - Siti Megayati; Indihadi, Dian; Saputra, Erwin Rahayu (COLLASE (Creative of Learning Students Elementary Education), 2024)
Writing is an activity that can explore one's thoughts and feelings about an object, choose what to write and write it down so that the reader will understand clearly. Writing can be said as one of the 4 aspects of language including listening, speaking, reading, and writing. According to Susanto (2013: 241) stated, language skills performed by humans in the form of listening, speaking, reading, and writing are capitalized by vocabulary, namely intellectual activity, the work of an educated human brain. Writing is the skill of a person (individual) communicating messages in a piece of writing. In accordance with the opinion of Susanto (2013: 248) stated "writing skills are activities of expressing ideas or ideas that are in our minds, pouring out our hearts through written language so that others can read and understand it. Judging from the opinion above, it can be found that writing skills are skills in expressing or expressing ideas or ideas in the form of written language so that other people can read and understand the intent of the writing. According to Kosasih (2019, p. 114) "explanatory text is a text that explains an event, be it a natural event, social and cultural event, or personal event". Based on these problems, the researcher has an alternative for fifth grade elementary school students, especially in Indonesian language lessons with material for writing explanatory texts. Researchers are interested in using the mind mapping learning method, to help and find out learning outcomes in the material of writing explanatory texts. Keywords: writing skills, explanatory text, mind mapping method